Delivering on the promises of wellbeing? Traidcraft Exchange's experiment with measuring wellbeing. Issue 5 (4th July 2022) - Adams, Mark; Williams, George
ABSTRACT: Improvements in "wellbeing" are frequently cited as the ultimate objective of "development". Efforts to operationalise wellbeing quickly turn to discussions of definition, assessment, and measurement. This article describes Traidcraft Exchange's ten-year work to assess changes in wellbeing resulting from their interventions. We outline the conceptual model Traidcraft adopted, how it was adapted, and how it has delivered on core promises of wellbeing. We explore how differing priorities influenced implementation and results. An explicit focus on wellbeing promises more complete information and positive, empowering, person-centred "development". Achieving both ambitions requires clear objectives and has implications for the methods and processes used.